2020
DOI: 10.1186/s13613-020-00668-6
|View full text |Cite
|
Sign up to set email alerts
|

Use, timing and factors associated with tracheal intubation in septic shock: a prospective multicentric observational study

Abstract: Background No recommendation exists about the timing and setting for tracheal intubation and mechanical ventilation in septic shock. Patients and methods This prospective multicenter observational study was conducted in 30 ICUs in France and Spain. All consecutive patients presenting with septic shock were eligible. The use of tracheal intubation was described across the participating ICUs. A multivariate analysis was performed to identify parameters associated with early intubation (before H8 following vasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…For example, after tracheal intubation in patients with type II respiratory failure, ETCO 2 is signi cantly increased due to the accumulation of carbon dioxide in the body. At this time, the value of ETCO 2 may not truly re ect the changes in circulation [20].…”
Section: Discussionmentioning
confidence: 97%
“…For example, after tracheal intubation in patients with type II respiratory failure, ETCO 2 is signi cantly increased due to the accumulation of carbon dioxide in the body. At this time, the value of ETCO 2 may not truly re ect the changes in circulation [20].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, our mixed-effects analysis showed that most of the variability for the need of invasive mechanical ventilation can be explained by baseline factors at admission, while differential "ICU culture" does not appear to play a major role in this decision. This needs to be analysed in comparison to previous research showing fairly strong centre effects, both in the care of patients with septic shock and mechanically ventilated critically ill adults 17,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, several studies have shown that the use of invasive mechanical ventilation remains high in patients with COVID-19, and patients usually receive it for long periods of time [13][14][15] . Although the decision to intubate is based on several clinical markers, including blood oxygenation 16 , ICUs may have different policies towards the initiation of invasive mechanical ventilation 17 . Based on experimental 18,19 and observational data 4,5 , a so-called "early approach" to invasive mechanical ventilation is advocated by some experts in patients with non-COVID-19 related ARDS 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients were included if they had positive con rmatory nasopharyngeal or pulmonary tract sample and received support with either HFNO or intubation on the rst day of ICU admission. Main exclusion criteria were intubation outside the ICU, a PaO /FiO 2 ratio > 300 mmHg, a respiratory rate on day 1 above 35 breaths/min, a Glasgow Coma Score lower than 13 and pH lower than 7.25 18,27 . The rationale for the aforementioned eligibility criteria was based on a population that (with equipoise) could theoretically be randomized to a strategy of early intubation or HFNO in the rst 24 hours of critical illness, under the framework of a target randomized trial (e-table 1).…”
Section: Study Populationmentioning
confidence: 99%
“…Conversely, several studies have shown that the use of invasive mechanical ventilation remains high in this population, and patients usually receive it for prolonged periods of time [14][15][16] . In daily clinical practice, the decision to intubate is usually based on several clinical markers -including blood oxygenation 17 -and may differ across institutions 18 .…”
Section: Introductionmentioning
confidence: 99%